FRI0165 PATIENT- AND PHYSICIAN-REPORTED OUTCOMES FROM RAJ4: A RANDOMISED, DOUBLE-BLIND, PLACEBO-CONTROLLED STUDY OF THE EFFICACY AND SAFETY OF PEFICITINIB (ASP015K) IN PATIENTS WITH RHEUMATOID ARTHRITIS (RA) WHO HAD AN INADEQUATE RESPONSE TO METHOTREXATE (MTX). (June 2019) - Tanaka, Yoshiya; Takeuchi, Tsutomu; Rokuda, Mitsuhiro; Izutsu, Hiroyuki; Kaneko, Yuichiro; Shiomi, Teruaki; Yamada, Emi
Abstract : Background: The novel oral Janus kinase inhibitor, peficitinib, demonstrated efficacy and tolerability as once-daily combination therapy with MTX for moderate-to-severe RA in the RAJ4 phase 3 study (NCT02305849 ). 1 For the first time, we focussed on patient and physician outcome measures in this Japanese study. Objectives: To assess health-related quality of life (HRQoL) of Japanese patients with RA who had an inadequate response to MTX. Methods: This multicentre, randomised, double-blind, parallel-group, placebo-controlled, phase 3 study recruited patients in Japan with active RA and inadequate response to MTX. 1 Patients were randomised 1:1:1 to 52-week placebo+MTX (PBO), peficitinib 100 mg QD+MTX (PEFI 100 mg) or peficitinib 150 mg QD+MTX (PEFI 150 mg). The PBO group was switched to PEFI 100 mg or 150 mg at Week 12 (for non-responders) or Week 28 (for remaining patients). Patient- and physician-reported outcome assessments included: Physician's Global Assessment of disease activity (PGA); Subject's Global Assessment of disease activity (SGA); and Subject's Global Assessment of pain (SGAP) by visual analogue scale. Physical function was evaluated using Health Assessment Questionnaire-Disability Index (HAQ-DI). All assessments were conducted at each visit from baseline to the end of study. Results: 519 patients were treated: PBO (n=170), PEFI 100 mg (n=175) and PEFI 150 mg (n=174). One PEFI 100 mg patient was excluded from the analysis due to protocol deviation. At Weeks 12/early termination (ET) and 28/ET, both PEFI groups were associated with significant improvements in PGA, SGA, SGAP and HAQ-DI (Table 1 ). These outcomes were maintained or improved at end of treatment (EOT; Week 52/ET), when mean change from baseline for PGA, SGA, SGAP and HAQ-DI in the PEFI 100 mg and PEFI 150 mg groups were: -38.41, -43.33; -29.34, -34.05; -28.94, -32.68; and -0.36, -0.51, respectively. Significantly greater proportions of patients achieved functional remission and a minimum clinically important (MCI) reduction in HAQ-DI score (≤0.5 and reduction of ≥0.22, respectively) at Weeks 12/ET and 28/ET in both PEFI groups than in the PBO group (p<0.001 vs PBO for both PEFI doses; Table 1 ). In the PEFI 100 mg and PEFI 150 mg groups at EOT, functional remission occurred in 105/172 (61.0%) and 106/171 (62.0%) patients and MCI reduction in HAQ-DI score occurred in 99/172 (57.6%) and 120/171 (70.2%) patients, respectively. Conclusion: Measures of PGA, SGA, SGAP and HAQ-DI in patients with RA who had an inadequate response to MTX demonstrated improved HRQoL with peficitinib; PEFI 150 mg QD showed similar or numerically greater changes in HRQoL than PEFI 100 mg QD. Improvements were maintained or improved to the EOT and demonstrated a significant benefit for patients with RA in Japan. Reference: [1] Takeuchi T, et al. Arthritis Rheumatol 2018; 70 (Suppl. 10): Abstract 888. Acknowledgement: This study was sponsored by Astellas Pharma, Inc. Medical writing support was provided by Rhian Harper Owen of Cello Health MedErgy and funded by Astellas Pharma, Inc. Disclosure of Interests: Yoshiya Tanaka Grant/research support from: Abbvie, Astellas, Bristol-Myers Squibb, Chugai, Daiichi-Sankyo, Eisai, Mitsubishi-Tanabe, MSD, Ono, Taisho-Toyama, Takeda, Speakers bureau: Abbvie, Asahi-kasei, Astellas, Bristol-Myers Squibb, Chugai, Daiichi-Sankyo, Eli Lilly, Eisai, Glaxo-Smithkline, Janssen, Mitsubishi-Tanabe, Novartis, Pfizer Japan Inc, Sanofi, Takeda, UCB, YL Biologics, Tsutomu Takeuchi Grant/research support from: Astellas Pharma Inc, Chugai Pharmaceutical Co, Ltd., Daiichi Sankyo Co., Ltd., Takeda Pharmaceutical Co., Ltd., AbbVie GK, Asahikasei Pharma Corp., Mitsubishi Tanabe Pharma Co., Pfizer Japan Inc., Eisai Co., Ltd., AYUMI Pharmaceutical Corporation, Nipponkayaku Co. Ltd., Novartis Pharma K.K., Grant/research support from: AbbVie, Asahi Kasei, Astellas, AstraZeneca, AYUMI, Bristol-Myers Squibb, Chugai, Daiichi Sankyo, Eisai, Eli Lilly Japan, Janssen, Mitsubishi Tanabe, Nippon Kayaku, Novartis, Pfizer Japan Inc, Taiho, Taisho Toyama, Takeda, Teijin, Grant/research support from: Astellas Pharma Inc., Bristol Myers Squibb, Chugai Pharmaceutical Co., Ltd., Mitsubishi Tanabe Pharma Co., Pfizer Japan Inc., Santen Pharmaceutical Co., Ltd., Takeda Pharmaceutical Co., Ltd., Teijin Pharma Ltd., AbbVie GK, Asahi Kasei Pharma Corp., Taisho Toyama Pharmaceutical Co., Ltd., SymBio Pharmaceuticals Ltd., Janssen Pharmaceutical K.K., Celltrion Inc., Nipponkayaku Co. Ltd., and UCB Japan, Consultant for: Astra Zeneca K.K., Eli Lilly Japan K.K., Novartis Pharma K.K., Mitsubishi Tanabe Pharma Co., Abbivie GK, Nipponkayaku Co.Ltd, Janssen Pharmaceutical K.K., Astellas Pharma Inc., Taiho Pharmaceutical Co. Ltd., Chugai Pharmaceutical Co. Ltd., Taisho Toyama Pharmaceutical Co. Ltd., GlaxoSmithKline K.K., UCB Japan Co. Ltd., Consultant for: AbbVie, Asahi Kasei, Astellas, AstraZeneca, AYUMI, Bristol-Myers Squibb, Chugai, Daiichi Sankyo, Eisai, Eli Lilly Japan, Janssen, Mitsubishi Tanabe, Nippon Kayaku, Novartis, Pfizer Japan Inc, Taiho, Taisho Toyama, Takeda, Teijin, Consultant for: Astra Zeneca K.K., Eli Lilly Japan K.K., Novartis Pharma K.K., Mitsubishi Tanabe Pharma Co., Asahi Kasei Medical K.K., AbbVie GK, Daiichi Sankyo Co., Ltd., Bristol Myers Squibb, and Nipponkayaku Co. Ltd., Speakers bureau: Astellas Pharma Inc., Bristol Myers Squibb, Chugai Pharmaceutical Co., Ltd., Mitsubishi Tanabe Pharma Co., Pfizer Japan Inc., Santen Pharmaceutical Co., Ltd., Takeda Pharmaceutical Co., Ltd., Teijin Pharma Ltd., AbbVie GK, Asahi Kasei Pharma Corp., Taisho Toyama Pharmaceutical Co., Ltd., SymBio Pharmaceuticals Ltd., Janssen Pharmaceutical K.K., Celltrion Inc., Nipponkayaku Co. Ltd., and UCB Japan, Speakers bureau: AbbVie, Asahi Kasei, Astellas, AstraZeneca, AYUMI, Bristol-Myers Squibb, Chugai, Daiichi Sankyo, Eisai, Eli Lilly Japan, Janssen, Mitsubishi Tanabe, Nippon Kayaku, Novartis, Pfizer Japan Inc, Taiho, Taisho Toyama, Takeda, Teijin, Speakers bureau: AbbVie GK., Bristol–Myers K.K., Chugai Pharmaceutical Co. Ltd., Mitsubishi Tanabe Pharma Co., Pfizer Japan Inc., Astellas Pharma Inc, Diaichi Sankyo Co. Ltd., Eisai Co. Ltd., Sanofi K.K., Teijin Pharma Ltd., Takeda Pharmaceutical Co. Ltd., Novartis Pharma K.K., Mitsuhiro Rokuda Employee of: Astellas Pharma, Inc., Hiroyuki Izutsu Employee of: Astellas Pharma, Inc., Yuichiro Kaneko Employee of: Astellas Pharma, Inc., Teruaki Shiomi Employee of: Astellas Pharma, Inc., Emi Yamada Employee of: Astellas Pharma, Inc.